Grafting of Aminoethylphosphonic Acid Monolayers on Titanium Nitride: The Effect of Surface Pretreatments through Electrochemical‐Assisted Oxidation. Issue 5 (12th December 2016) - Zeb, Gul; Le, Xuan Tuan
Abstract : The surface of titanium nitride (TiN) contains, in addition to nitride compounds, a certain amount of native oxide. This oxide allows the functionalization of TiN with amine‐terminated groups through spontaneous self‐assembly of aminoethylphosphonic acid. However, real industrial applications of titanium nitride, particularly for microelectronics and electrochemistry, require the development of efficient methods to improve the aminoethylphosphonate loading while preserving the main intrinsic characteristics of the TiN substrate. It is demonstrated that surface pretreatment, by either electrochemical anodization or cleaning in H2 O2 :HCl:H2 O mixture, considerably enhances the phosphonic loading. This is the first report on mild oxidation of TiN surface using an acidic peroxide mixture. This electrochemical‐assisted method does not require any electrochemical equipment, and works through simple immersion of the TiN surface in the cleaning solution at room temperature. Moreover, cleaning in this solution leads to a significantly increased quantity of the grafted phosphonate groups via uniform hydroxylation of the entire surface, without altering the behavior of the pristine TiN. The electrochemical anodization technique, which results in quasicomplete conversion of surface TiN compounds to TiO2 under our working conditions, needs further fundamental investigation towards incorporation of oxygen into the TiN lattice. Abstract : A "mild" pretreatment of a titanium nitride surface in acidic peroxide solution promotes self‐assembly of a phosphonate monolayer bearing amine functional groups. The high density of amine functionalities attained through this pretreatment can further be exploited towards biosensors, microelectronics processing, metal deposition, etc. This pretreatment method is scalable, industrially feasible, simple, and proves more efficient than other pretreatments based on electrochemical anodization.